A relação entre o tecnoestresse, o uso das tecnologias e o sofrimento psíquico - Bach, Daiane Libero (2024)
The present research investigates the relationship between technostress, the use of technologies, and the psychological suffering of faculty members in the humanities courses at the State University of Western Paraná - Francisco Beltrão Campus, highlighting psychoanalytic contributions to the practices of technology use in teaching. We conducted a bibliographic survey in Brazilian universities to identify the quantity and nature of the research developed on technostress and the psychological suffering of faculty members, integrating the psychoanalytic perspective. Our focus is to discuss technostress in academic spaces. The databases selected for the research and theoretical-bibliographic review were the Brazilian Digital Library of Theses and Dissertations (BDTD), the Catalog of Theses and Dissertations (CAPES), and the Scientific Electronic Library Online (SCIELO). We found thirty-two dissertation productions and four theses related to the theme. The justification for our research lies in the scarcity of studies that address psychoanalysis correlated with technostress in teaching. In the theoretical foundation, we provide a brief contextualization on technology and teaching. From the perspective of historical and dialectical materialism, we present the historical context from a social perspective. Throughout the research, we highlight the influence of Information and Communication Technologies (ICT) in the teaching environment, addressing the possibilities of their use as pedagogical support to understand our research object. Finally, we focus on the technostress diagnosis methodology supported by the RED/TIC tool, the Technostress Scale, and present the results obtained from the tests conducted at the university and the analysis of technostress through different combinations of results. Additionally, we seek to identify the main sources of technostress among faculty members and analyze how these sources affect the performance and well-being of teachers. We investigate the triggering factors of technostress, such as information overload, pressure to adapt to new technologies, the constant need for professional updating, and the lack of institutional support.